Preliminary nutritional content analysis of commercialized Malaysian edible bird nest - Joefrey, Stalin; Azmi, M. A.; Ideris, Aini; Ismail, Intan Safinar; Abas, Faridah; Md. Ajat, Mohd Mokrish; Mansor, Rozaihan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
This study investigated the chemical and mineral compostions of the commercialized edible bird’s nests (EBN) of Aerodramus fuciphagus that have been bought from the local health store in Malaysia. The chemical and mineral compositions were determined according to the official Association of Official Agricultural Chemists (AOAC) methods and spectroanalytical procedure using atomic absorption spectroscopy (AAS) respectively. The results revealed that the commercialized EBNs examined mainly consisted of protein (46.59%) with 381.49 mg/g protein of essential amino acids, carbohydrates (39.84%), moisture content (8.77%), ash content (3.89%), fibre content (0.53%) and crude fat content (0.38%). The main amino acid constituents in the studied commercialized EBN were arginine (51.44%) followed by methionine + cysteine (13.58%) while alanine (1.92%) and gylcine (2.01%) were among the least constituents of amino acids. Major mineral elements detected from Malaysian EBN were calcium (Ca), iron (Fe), potassium (K) and sodium (Na). This study revealed preliminary results on the nutritional content of commercialized Malaysian EBN which were attributed by many factors and further studies on nutritional attributes of raw, cleaned Malaysian EBN can be done in comparison to this study.